The The Influence Of Media On Teenagers In Choosing Panjang Beach For Tourism In The Digital Era - Safitri, Widya; Widiyarti, Diyas; Nopianti, Heni (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Abstract: Social media has become essential for tourism promotion in this digital era. This research analyses the influence of social media platforms on tourism promotion in Bengkulu, using James S. Coleman's rational choice theory. This research uses a closed questionnaire given to 90 students who use social media to find a tourism destination. The analysis technique used is multiple linear regression analysis and percentage descriptive statistics. The results showed that the review of social media posts significantly influenced teenagers' interest in visiting a destination. 52.22% of respondents prefer Instagram as their travel reference, supported by reviews of tourist destinations in promotional posts. Tourism destinations that are active and creative in utilizing social media and have good reviews tend to have a higher level of interaction with potential tourists. The results of this study guide tourist destinations and tourism marketers to maximize the potential of social media in their promotion.